Value chains in construction based on the concept of lean manufacturing in the conditions of digital transformation - K. Yu. Kulakov; A. K. Orlov; V. S. Kankhva (Vestnik MGSU)
Introduction. In modern conditions, the fundamental basis of construction is the process of creating value of the capital construction object for the consumer. The article examines the process of creation of capital construction projects as a value chain and substantiates the influence of digital transformation on the development and dynamics of this chain. The analysis of modern research on the impact of digitalization on value chains is carried out, the results of the analysis are projected onto the processes of digital transformation of the construction ecosystem. The main existing problems of project implementation efficiency in construction, including from the position of the actual task of increasing labour productivity, as well as the prospects for digitalization of construction from the position of value chains using the tools of the lean manufacturing concept are identified. A mechanism for implementing the concept of lean manufacturing in construction using digitalization tools is proposed. Based on the results of the financial and economic analysis, the effects of the implementation of the proposed measures that affect the timing of the implementation of the IСP, cost and quality parameters are calculated. The proposed approach contributes to the creation of a database on the occurrence and ways to solve problems in business processes, as well as creates opportunities for continuous training and motivation of employees, which is fully consistent with the need for continuous improvement in lean construction.Materials and methods. The methodological basis of the study is the concept of lean construction in relation to aspects of the transformation of the digital construction ecosystem. In addition, systematic and situational approaches, methods of qualitative, comparative and factor analysis of the results of foreign and domestic experience were used in the study. The tools of investment analysis and financial and economic modelling were used to analyze the results of the implementation of lean construction tools within the framework of investment and construction projects.Results. The authors propose a practical approach to the implementation of the concept of lean production using digitalization tools in the activities of a construction company. The analysis of the results of the introduction of digital tools based on the concept of lean construction in Russia made it possible to quantify the losses in the framework of the implementation of investment and construction projects, as well as to calculate the effects of the implementation of the proposed solutions.Conclusions. The study recommends participants of the construction ecosystem to implement the concept of lean construction in integration with digital technologies in accordance with the proposed practical approach to increase labour productivity and the efficiency of investment projects implemented.